2017
DOI: 10.5957/jspd.150027
|View full text |Cite
|
Sign up to set email alerts
|

On the Interfoil Spacing and Phase Lag of Tandem Flapping Foil Propulsors

Abstract: The aim of this article is to provide a theoretical basis upon which to advance and deploy novel tandem flapping foil systems for efficient marine propulsion. We put forth three key insights into tandem flapping foil hydrodynamics related to their choreography, propulsive efficiency, and unsteady loading. In particular, we propose that the performance of the aft foil depends on a new nondimensional number, s/Uτ, which is the interfoil separation s normalized by the distance that the freestream U advects in one… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…The striking band structures that were first reported in the study of Boschitsch [1] for in-line foils, can be observed in not only two-dimensional interactions here, but also in three-dimensional interactions. This is expected though since the performance of the follower is highly dependent upon the synchrony between the propulsor motion and the impinging vortex street, which can be described as a spatial instead of temporal synchrony as, φ spatial = φ − 2πX * /λ * , [36,37]. Here λ * is the wake vortex wavelength normalized by the chord length of the propulsors.…”
Section: Propulsive Performance Of the Leader And Followermentioning
confidence: 99%
“…The striking band structures that were first reported in the study of Boschitsch [1] for in-line foils, can be observed in not only two-dimensional interactions here, but also in three-dimensional interactions. This is expected though since the performance of the follower is highly dependent upon the synchrony between the propulsor motion and the impinging vortex street, which can be described as a spatial instead of temporal synchrony as, φ spatial = φ − 2πX * /λ * , [36,37]. Here λ * is the wake vortex wavelength normalized by the chord length of the propulsors.…”
Section: Propulsive Performance Of the Leader And Followermentioning
confidence: 99%
“…Yet, for a tandem set-up, the choice of a particular should be also taken into account. Indeed, flipper phasing has been shown to impact the hind foil's efficiency in various tandem foil concepts (Arranz et al., 2020; Broering & Lian, 2015; Epps, Muscutt, Roesler, Weymouth, & Ganapathisubramani, 2017; Muscutt et al., 2017b; Xu, Duan, & Xu, 2017). Therefore, proper alignment of the aforementioned parameters might result in further gains within this area.…”
Section: Resultsmentioning
confidence: 99%